2019
DOI: 10.1038/s41467-019-08287-x
|View full text |Cite
|
Sign up to set email alerts
|

TAZ couples Hippo/Wnt signalling and insulin sensitivity through Irs1 expression

Abstract: Insulin regulates blood glucose levels by binding its receptor and stimulating downstream proteins through the insulin receptor substrate (IRS). Impaired insulin signalling leads to metabolic syndrome, but the regulation of this process is not well understood. Here, we describe a novel insulin signalling regulatory pathway involving TAZ. TAZ upregulates IRS1 and stimulates Akt- and Glut4-mediated glucose uptake in muscle cells. Muscle-specific TAZ-knockout mice shows significantly decreased Irs1 expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…The two arms downstream of insulin/IGF, PI3K and MAPK signalling pathways are altered in T2D and CRC. Crosstalk between PI3K and Wnt signalling through GSK3B inactivation or between Wnt and Hippo through YAP/TAZ and their regulation by metabolites illustrates the importance of their correct wiring for signalling in T2D and CRC (Santinon et al 2016, Hwang et al 2019. Furthermore, leptin/adiponectin imbalances enhance JAK/STAT signalling as inflammatory cytokines do, reinforcing the link with CRC.…”
Section: Remodelling Crc Cell Signalling By Hormonal Alterations In T2dmentioning
confidence: 99%
“…The two arms downstream of insulin/IGF, PI3K and MAPK signalling pathways are altered in T2D and CRC. Crosstalk between PI3K and Wnt signalling through GSK3B inactivation or between Wnt and Hippo through YAP/TAZ and their regulation by metabolites illustrates the importance of their correct wiring for signalling in T2D and CRC (Santinon et al 2016, Hwang et al 2019. Furthermore, leptin/adiponectin imbalances enhance JAK/STAT signalling as inflammatory cytokines do, reinforcing the link with CRC.…”
Section: Remodelling Crc Cell Signalling By Hormonal Alterations In T2dmentioning
confidence: 99%
“…Understanding how beige selective pathways are induced can provide new insights that could allow for the targeted selection of this metabolically favorable phenotype of adipocyte. Although developmentally of different origin (muscle-like), YAP/TAZ signalling has also been shown to regulate insulin signalling in muscle where TAZ has shown to stimulate insulin sensitivity by upregulating IRS1 which mediates GLUT4 uptake of glucose in muscle cells [97]. Brown adipocytes (BAT) are functionally similar to beige adipocytes.…”
Section: Obesitymentioning
confidence: 99%
“…Previous studies revealed that Wnt/β-catenin signaling regulates IRS-1 through β-catenin/TCF4 binding to the regulatory sequence of the murine IRS-1 promoter in mouse skeletal muscle C2C12 cells and rat H4IIE hepatoma cells (Hwang et al, 2019;Yoon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%